Baccaurea angulata fruit juice reduces atherosclerotic lesions in diet-induced Hypercholesterolemic rabbits - Ibrahim, Muhammad; Ahmed, Idris Adewale; Abimbola, Maryam Mikail; Ishola, Afeez Adekunle; Draman, Samsul; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (BioMed Central Ltd., 2017)
Background: Atherosclerosis is the most common disease of large and medium-sized arteries linked to oxidative stress, dyslipidemia as well as chronic inflammation. The aim of this study was to evaluate the potential health benefits of Baccaurea angulata (BA) fruit juice on the aorta of diet-induced hypercholesterolemic rabbits, to detect an accumulation of fatty streak and evaluate the percentage of atherosclerotic lesion accrued.